The irreversibility of thiamin transport in Saccharomyces cerevisiae - Ruml, T; Silhánková, L; Rauch, P (Folia microbiologica, 1988)
Neither exit nor counterflow efflux of thiamin, taken up previously by an active transport, were found in Saccharomyces cerevisiae, in either the wild type or a mutant with a lower rate of thiamin phosphorylation. Complete inhibition of thiamin phosphorylation by oxythiamin did not lead to any release of thiamin taken up by the cell.
Keywords: Saccharomyces cerevisiae; Oxythiamine; aktivní transport; Phosphorylation; mutace; thiamin; Biological Transport, Active; Kinetics; Mutation; Thiamine; fosforylace; kinetika; oxythiamin